Biological observations and first stranding record of Mesoplodon peruvianus from the central Pacific coast of Oaxaca, Mexico - Jesús García-Grajales (Therya, 2017)
The knowledge of Mesoplodon peruvianus species about its distribution and ecology is limited, because the range of the species is unknown. Mainly due to their inconspicuous behaviour. A survey was conducted from November 2014 to January 2015 along a near 80 km long transect in the central coast of Oaxaca. Additionally, based on an stranded individual at Zicatela beach, we measured it and performed a necropsy to report the probable cause of stranding. Two individuals of M. peruvianus species were observed on December 5, 2014 at about 9.3 km from the coast at 12:45 local time. The identification was clearly positive because of the black and white large individual, with an estimated size of 4 m. This is the first record of M. peruvianus in the area. On March second 2016, a carcass of a male of M. peruvianus was found stranded at Zicatela beach; was classified as scale 2 stranded individual (freshly dead). Our main pathological findings were related with the respiratory and the digestive systems. The thoracic cavity arose out of air suggesting a pneumothorax; lungs were collapsed and to the touch showed a consistency of atelectasis. In total, 18 marine mammal species have been recorded for the state of Oaxaca, this study adds a new record, confirming the presence of M. peruvianus and its distribution in the region. The collapsed lungs of the stranded individual, probably resulted from an apnea state, were related with dysbarism. In Mexico no exist the practice of necropsies in wild marine mammals, therefore, our work contributes to gather relevant information on the health of marine mammals and the threats they face.